Synthesis and crystallographic, spectroscopic and computational characterization of 3,30,4,40-substi-tuted biphenyls: Effects of OR substituents on the intra-ring torsion angle - Vadra, Nahir; Suarez, Sebastian; Slep, Leonardo Daniel; Manzano, Veronica Elena; Halac, Emilia B.; Baggio, Ricardo F.; Cukiernik, Fabio Daniel (International Union of Crystallography, 2020)
Fil: Vadra, Nahir. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química, Física de los Materiales, Medioambiente y Energía. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Química, Física de los Materiales, Medioambiente y Energía; Argentina